2011
DOI: 10.1016/j.cvsm.2011.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Canine Noroviruses

Abstract: Noroviruses are recognized as emerging enteric pathogens of humans and have been identified in recent years in a number of mammalian species. The role of noroviruses as pathogens in immune-competent animals and under natural conditions remains uncertain, although both homologous and heterologous animal models are now available to investigate the pathogenesis, the immune response, and the molecular mechanism regulating norovirus infection. Recently, evidence has been gathered that noroviruses may also circulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…Porcine NoVs are classified in distinct genotypes within GII, bovine and ovine viruses belong uniquely to GIII, and murine NoVs are grouped in GV. Recently, several research groups have reported NoVs in domestic carnivores with diarrhea [10,11]. Canine NoVs (CaNoVs) genetically related to GIV have been reported in Italy, Greece and Japan [10-13], whereas viruses belonging to a proposed new genogroup (GVI) were found in fecal samples from dogs with diarrhea in Portugal and Italy [9,14-16].…”
Section: Introductionmentioning
confidence: 99%
“…Porcine NoVs are classified in distinct genotypes within GII, bovine and ovine viruses belong uniquely to GIII, and murine NoVs are grouped in GV. Recently, several research groups have reported NoVs in domestic carnivores with diarrhea [10,11]. Canine NoVs (CaNoVs) genetically related to GIV have been reported in Italy, Greece and Japan [10-13], whereas viruses belonging to a proposed new genogroup (GVI) were found in fecal samples from dogs with diarrhea in Portugal and Italy [9,14-16].…”
Section: Introductionmentioning
confidence: 99%
“…NoV is classified into at least five genogroups (GI, GII, GIII, GIV and GV) based on their VP1 sequences . Additional genogroups (GVI and GVII) have recently been proposed . GI, GII, GIV and GVI are known to infect humans; of these, GII is the most prevalent .…”
mentioning
confidence: 99%
“…Specifically, bovine NoVs are found in GIII, swine NoVs in GII (clusters GII.11, GII.18, and GII.19), and murine NoVs in GV. Canine NoVs were first reported in Italy in 2008 (5) and have since been found in other European countries (4,(6)(7)(8)(9). So far, all canine NoVs belong to GIV and the tentative new GVI (7).…”
mentioning
confidence: 99%